Le Labo des Héritiers : Bakker, Scarpa, Van Severen, Vermeersch - Busine, Laurent; Vander Gucht, Daniel; Holthof, Marc (Antwerpen : Luster, 2014)
This catalog is published by Luster and Grand-Hornu Images within the framework of the exhibition Le Labo des Héritiers, from September 21st 2014 till January 4th, 2015 in Grand-Hornu.
Frans
Engels
Nederlands
kunstcatalogus
Keywords: Van Severen; Vermeersch